(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Disability has been defined as “any restriction or lack of ability toperform an activity in the manner or within the range considered normal for ahuman being. The major preventable causes of disabilities are malnutrition,communicable diseases, early childhood infections and accidents at home andwork place. Early detection of impairment, combined with early and effectivecurative care can make a significant impact in minimizing or compensating forimpairment and its consequences. There was no comprehensive study on theattitudes of society towards disabled children in rural India which has necessitatedus for this study to make suggestions to the institutions involved for thepositive attitudes. Societal attitudes towardspersons with disability have changed from time to time. Various factorscontribute to these changing attitudes. A comparativeinternational project on disability attitudes, beliefs and behaviours wascarried out in India in collaboration with partner institutions andresearchers. This paper presents an overview of the preliminary findings acrossall communities, and includes information on sample and scale characteristics,and scale distributions.